Asymmetric Effect of Oil Prices on Export Performance: The Role of Export Financing Schemes in Pakistan - Kousar, Shazia; Khalid, Iqra; Ahmed, Farhan; Ramos-Requena, Jose Pedro (International Journal of Energy Economics and Policy, 2022)
This study aims to check the impact of export financing (EF) schemes like EF-25, oil prices, exchange rate, and foreign direct investment on export performance in Pakistan. Study utilized textile exports and non-textile exports to measure the export performance in Pakistan. Data for modeled variables are taken from the State Bank of Pakistan (SBP), and International Financial Statistics (IFS) for the period of 2004 to 2020. This study employed Auto Regressive Distributive Lags (ARDL) and Non-Linear Auto Regressive Distributive Lags (NARDL) models from 2004 to 2020 to check the symmetric and asymmetric impact of modeled variables on export performance in Pakistan. It is observed that there is a positive and significant impact of export financing schemes and oil prices on the performance of the export of Pakistan in both time regimes before and after the world financial crisis 2008. Asymmetric effects showed that positive shock in oil prices leads to a positive change in exports and negative shock also leads to a positive change in exports. The impact of export financing on the textile sector is significant and positive but it is insignificant in the case of oil prices. Whereas the impact of oil prices on non-textile exports of Pakistan is significant and a positive rather insignificant impact of export financing is found for non-textile exports. According to the results, export financing is favorable for Pakistan’s export performance so it should be encouraged and more schemes should be introduced.